2021
DOI: 10.3390/cells10102547
|View full text |Cite
|
Sign up to set email alerts
|

miR-21-3p/IL-22 Axes Are Major Drivers of Psoriasis Pathogenesis by Modulating Keratinocytes Proliferation-Survival Balance and Inflammatory Response

Abstract: Psoriasis is a chronic inflammatory skin disease that is mediated by complex crosstalk between immune cells and keratinocytes (KCs). Emerging studies have showed a specific psoriatic microRNAs signature, in which miR-21 is one of the most upregulated and dynamic miRNAs. In this study, we focused our investigations on the passenger miR-21-3p strand, which is poorly studied in skin and in psoriasis pathogenesis. Here, we showed the upregulation of miR-21-3p in an IMQ-induced psoriasiform mouse model. This upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…These results suggest that miR-21-3p may play a promoting role in psoriasis, consistent with previous study. 17 The role of miR-21-3p in psoriasis is consistent with the role of miR-21-5p in psoriasis. 21,22 Moreover, miR-21-3p mimics could promote DNA replication and promote the G1 phase of the cell cycle, indicating that miR-21-3p may mediate abnormal changes in HaCaT cell proliferation by regulating the G1 phase of the cell cycle.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…These results suggest that miR-21-3p may play a promoting role in psoriasis, consistent with previous study. 17 The role of miR-21-3p in psoriasis is consistent with the role of miR-21-5p in psoriasis. 21,22 Moreover, miR-21-3p mimics could promote DNA replication and promote the G1 phase of the cell cycle, indicating that miR-21-3p may mediate abnormal changes in HaCaT cell proliferation by regulating the G1 phase of the cell cycle.…”
Section: Discussionsupporting
confidence: 61%
“…20 Additionally, the miR-21–3p is shown to be a major driver for the pathogenesis of psoriasis. 17 However, its role in psoriasis is emerging. In this study, we found that miR-21-3p mimics promoted the proliferation and inhibited apoptosis of HaCaT cells, while miR-21-3p inhibitor showed the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2014) showed that impaired activation of IL-6/signal transducer and activator of transcription 3 pathway in epidermal lesions of patients with psoriasis could trigger the upregulation of miR-21-5p, which in turn leads to activation of TACE/ADAM17. In line with these studies, we recently identified IL-22 as a potent inducer of miR-21-5p expression ( Abdallah et al., 2021 ) and showed that the passenger miR-21-3p strand, in addition to the mature miR-21-5p strand, positively regulates KC proliferation through the upregulation of cyclin D1. Interestingly, Wang et al.…”
Section: Introductionmentioning
confidence: 63%